THE APPLICATION OF SPIRITUAL VALUES IN A COGNITIVE FRAMEWORK FOR COPING WITH STUDENTS' ACADEMIC STRESS - Imaniyatul Fithriyah (LP2M IAI Al-Khairat Pamekasan, 2026)
Academic stress is a significant challenge faced by students in Islamic boarding schools, considering the pressures from high academic demands and strict discipline. This study aims to analyze the role of integrating spiritual values into students' coping thoughts as a strategy to manage academic stress. Through a qualitative approach, data were collected via in-depth interviews, observations of students, and document studies at the Al-Majidiyah boarding school. The collected data were then analyzed using thematic analysis, which includes: a) initial coding, marking data segments relevant to spirituality-based coping; b) theme grouping, organizing emerging codes into main themes; and c) theme interpretation. The research results indicate that spiritual values, such as sincerity, trust in God (tawakkul), patience, and gratitude, play a crucial role in helping students manage academic stress. Students who apply these values in their thoughts and behavior report lower stress levels, better emotional calmness, and higher resilience in facing academic pressures. Religious guidance and mentorship from boarding school advisors also have a significant influence in directing students to use spiritual values as an effective coping strategy. The integration of spiritual values into coping thoughts has been shown not only to help alleviate academic stress but also to enhance students' learning motivation and discipline. This study concludes that spiritual values can be an effective approach to supporting the mental and spiritual well-being of students in the Al-Majidiyah boarding school environment in Pamekasan.